Sé an Saol an Máistir - Ó Fínneadha, Learaí Phádraic Learaí,Denvir, Gearóid (Cló lar-Chonnacht, 2010)
The entire poetic works of Learaí Phádraic Learaí Ó Fínneadha, edited by Gearóid Denvir.
Description based on publisher supplied metadata and other sources